The Linguistic Context and Context principles, Baxtiar Ali's drama (the clouds of Daniel) as a sample - Omed Barzan Brzw; Omer Ahmed Aziz (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
The title of the research is (The Linguistic Context and Context principles, Baxtiar Ali's drama (the clouds of Daniel) as a sample). The research consists of three sections: The first section introduces the concept of linguistic context, the definition of context, the emergence of linguistic context with the reason behind its emergence, and the function of linguistic context. The second section mentions the context principles in accordance with linguistic context which is a condition to be available in every context so as to be considered as an approved context. The third section identifies some of the context principles in Baxiar Ali's drama (the clouds of Daniel). Finally, the research ends with the most important conclusions, list of references and the abstract in English.